STUDENTS' POLITENESS UTILIZED BY STUDENTS IN ISLAMIC BOARDING SCHOOLS BASED ON THE MADURA CULTURE PERSPECTIVE - wildan; Aceng Rahmat; Endry Boeriswati (English Education Department, 2022)
Politeness strategies are crucial to communicate with others in the community. This research aims to describe the politeness principle in students' language from the perspective of Madura culture in an Islamic boarding school environment. This research uses qualitative and descriptive research methods to present data directly obtained through recording. The subjects of the study were students and lecturers of the Al Karimiyyah Islamic Boarding School Sumenep. The data were collected by transcribing the conversation between students, teachers, and principals. The results of this study indicate that some sacred words contradict the principle of politeness in the cultural perspective of the Madurai community, especially at the level of the use of Madurai, including Engghih-Bunten, Enggih-enten, and Enjek-Iye. The politeness of the students’ language use in the Islamic Boarding School is influenced by the social background, circumstances, and the combination of boarding school and Madura cultures.